(untitled) (Research, Society and Development, 2021)
The social educator is the main protective and affective reference for children and adolescents in care. It is essential, therefore, that these professionals are continuously qualified. The objective of this study was to evaluate the viability of Programa Cuida, a program to improve the positive educational practices for social educators in residential care. The program consists of eight-weekly sessions that work on topics such as assertive communication, conflict resolution strategies, emotional self-regulation and self-care practices. The program was applied in two groups, totaling 12 social educators and the feasibility criteria analyzed were: Acceptability/adherence; Observers’ evaluation of the moderator; Participants’ satisfaction with the Program and moderator; Understanding/generalization of contents. Descriptive statistics analyzes and a qualitative data analysis plan were used, based on the records of observers, participants and moderator. The results obtained were satisfactory considering the evaluated criteria and the changes introduced in the program are presented. This study demonstrates the viability of the proposal to proceed to efficacy trial.